Mobilização social para vigilância e controle do aedes aegypti à luz da determinação social da saúde: da universidade à cidade - Gonzaga, Eunir Augusto Reis (2022)
Tracking and controlling the Aedes aegypti mosquito is necessary because it is a vector for several diseases for which there are neither medicines nor vaccines. For this, we need to understand not only its modus operandi, the environmental factors that contribute to it, and the diseases characteristics but also the way of life of the human populations in their habitats The virus transmission is facilitated by these ways of life, as they are historically determined and socially embedded. The disease control framework used by the Health Department is based firmly on the conception of biological determination with an exclusive focus on the individual, and because of this, it cannot succeed in halting disease transmission by the Aedes aegypti. For this reason, we recommend a change in this framework, for it to include the social determination process and collective preventive strategies, aided by social mobilization and intersectionality. The goal of this dissertation is to discuss the tracking and controlling processes inside a social determination framework, epistemologically based on dialectics and critical realism. We propose social mobilization as a way to sensitize the community and promote health, as this makes people able to contribute to the tracking process where they live and work. Our results show that it is possible to mobilize people in a way that makes them engaged in the task of protecting the health of the community by actively searching for mosquito nests in the places that they live, which contributes to public health. We also concluded that dialectical materialism and critical realism are adequate methods to better understand the problem and propose more efficient for its solution. This experiment executed at the Campi of the Federal University of Uberlandia can also be applied to the city. Basic schools can engage their students in the social mobilization for the control of the mosquito. But for it to happen, it is necessary to go beyond the modern epidemiological models that are based on individual prevention and into the social determination framework, with its health promotion strategies to build environments that can make the city healthier.